Analisa Teknis dan Ekonomis Perawatan Terencana Kapal KM.Mutiara Ferindo 5 Roro 9000GT - Rekiana Jati Kusuma; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In this case it refers to the purpose of the content in this final project, namely by compiling a schedule for the Implementation of KM.Mutiara Ferindo 5 Ship Maintenance during the docking process at the PT.PAL Indonesia shipyard. Making a schedule includes what components are repaired when the ship is in a condition shipyard, make a ship maintenance management schedule that has been carried out in the shipyard. The data used in this thesis are data from PT.Antosim Lampung Pelayaran Surabaya and the researchers themselves. The type of data used in this research is primary data. will be related to the problem being studied and the results of the questionnaire distributed to several employees related to this research. In carrying out repairs there is a work list that shows how many items of work work must be done. So this work list has been approved to be carried out in the ship repair process. KM ship repair work. Mutiara Ferindo 5 which carries out planned repairs both at the shipyard and when the ship anchors at sea carries out maintenance technically and economically. Repair work on RO-RO ships that carry out maintenance on a scale that has been determined by the office and ship crew who are authorized to help carry out ship repairs. Repair work on the ship KM. Mutiara Ferindo 5 is well planned in terms of safety equipment and also component equipment that plays an important role in the smooth operation of the ship (maintenance of the entire engine room, deck, safety equipment and maintenance of the inside and outside of the ship). Implementing an economical system of estimating the remaining funds after maintenance at the shipyard.